Depletion of the receptor for advanced glycation end products (RAGE) sensitizes towards apoptosis via p53 and p73 posttranslational regulation - Brune, Maik; Müller-Schilling, Martina; Bierhaus, Angelika; Schilling, Tobias; Nawroth, Peter Paul (Oncogene, 2013)
The receptor for advanced glycation endproduct (RAGE) is involved in diabetic complications and chronic inflammation, conditions known to affect the sensitivity towards apoptosis. Here, we studied the effect of genetically depleting RAGE on the susceptibility towards apoptosis. In murine osteoblastic cells, RAGE knockout increased both spontaneous and induced apoptosis. Decreased levels of B-cell lymphoma 2 protein and increased intrinsic apoptosis were observed in Rage−/− cells. Furthermore, loss of RAGE increased expression of the death receptor CD95 (Fas, Apo-1), CD95-dependent caspase activation and extrinsic apoptosis, whereas NF-kB-p65 nuclear translocation was diminished. Importantly, depletion of RAGE reduced the ubiquitination and degradation of p53 and p73 and increased their nuclear translocation. The increase of p53 and p73 transactivational activity was essential for the RAGE-dependent regulation of apoptosis, because knockdown of p53 and p73 significantly decreased apoptosis in RAGE-deficient but not in RAGE-expressing cells. Thus, the RAGE-mediated posttranslational regulation of p53 and p73 orchestrates a sequence of events culminating in control of intrinsic and extrinsic apoptosis signaling pathways.